2002
DOI: 10.1152/ajpendo.00486.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of PDK1 in insulin-signaling pathway for glucose metabolism in 3T3-L1 adipocytes

Abstract: To investigate the role of 3-phosphoinositide-dependent protein kinase 1 (PDK1) in the insulin-signaling pathway for glucose metabolism, wild-type (wt), the kinase-dead (kd), or the plecstrin homology (PH) domain deletion (⌬PH) mutant of PDK1 was expressed using an adenovirus gene transduction system in 3T3-L1 adipocytes. wt-PDK1 and kd-PDK1 were found in both membrane and cytosol fractions, whereas ⌬PH-PDK1, which exhibited PDK1 activity similar to that of wt-PDK1, was detected exclusively in the cytosol frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…These results indicate that the insulin-mediated activation of PI-3 kinase is not sufficient to produce the levels of cellular PtdIns(3,4,5)P 3 needed to recruit PDK-1 and activate Akt and suggest that the transient increase of ROS may play a pivotal role in increasing PtdIns(3,4,5)P 3 levels. Consistent with this possibility, our data demonstrate that inhibition of insulin-mediated ROS production in SK-N-SH cells by using DPI results in a decrease of PDK-1 translocation to the membrane fraction and reduced Akt activation without significant effect on PI-3 kinase activity, although several reports showed that the subcellular localization of PDK-1 seem to be growth factor insensitive (Yamada et al, 2002;Kim et al, 2003) and that PDK-1 is activated through a PI-3 kinase-independent pathway (Kim et al, 2003). However, a recent report demonstrated that Akt cannot be activated by insulin-like growth factor-1 in homozygous knockin embryonic stem cells expressing a form of PDK-1 with a mutation in its PH domain that abolishes Membrane fractions and lysates were prepared from cells stimulated with insulin, insulin plus DPI, or insulin plus LY294002.…”
Section: Discussionsupporting
confidence: 86%
“…These results indicate that the insulin-mediated activation of PI-3 kinase is not sufficient to produce the levels of cellular PtdIns(3,4,5)P 3 needed to recruit PDK-1 and activate Akt and suggest that the transient increase of ROS may play a pivotal role in increasing PtdIns(3,4,5)P 3 levels. Consistent with this possibility, our data demonstrate that inhibition of insulin-mediated ROS production in SK-N-SH cells by using DPI results in a decrease of PDK-1 translocation to the membrane fraction and reduced Akt activation without significant effect on PI-3 kinase activity, although several reports showed that the subcellular localization of PDK-1 seem to be growth factor insensitive (Yamada et al, 2002;Kim et al, 2003) and that PDK-1 is activated through a PI-3 kinase-independent pathway (Kim et al, 2003). However, a recent report demonstrated that Akt cannot be activated by insulin-like growth factor-1 in homozygous knockin embryonic stem cells expressing a form of PDK-1 with a mutation in its PH domain that abolishes Membrane fractions and lysates were prepared from cells stimulated with insulin, insulin plus DPI, or insulin plus LY294002.…”
Section: Discussionsupporting
confidence: 86%
“…Support for an insulin effect comes from in vitro studies showing that insulin increases phosphorylation and catalytic activity of PDK-1 in isolated rat adipocytes (32) and skeletal muscle cells (44). However, some studies indicated that PDK-1 is a constitutively active enzyme whose catalytic activity is not stimulated by growth factors such as insulin or IGF-1 in 293 cells or CHO cells or 3T3-L1 adipocytes (45)(46)(47)(48)(49). The difference may be due to differences in the type of cells or assay methodology in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of other genes have also been implicated in insulin signalling and glucose metabolism in peripheral tissues. These include glycogen synthase kinase (GSK)-3 (Cline et al 2002, Hojlund et al 2003, Patel et al 2008, phosphoinositide-dependent kinase (PDK)-1 (Yamada et al 2002, Hashimoto et al 2006, Bayascas et al 2008, insulin-like growth factor-binding protein 1 (IGFBP1; Qiu et al 2005) and phosphoenolpyruvate carboxykinase (PEPCK; Franckhauser et al 2006).…”
Section: Introductionmentioning
confidence: 99%